Proceedings 1998 Asia Pacific Software Engineering Conference (Cat. No.98EX240)
DOI: 10.1109/apsec.1998.733616
|View full text |Cite
|
Sign up to set email alerts
|

High performance technique for ultrareliable execution of tasks under both hardware and software faults

Abstract: Various studies have shown that both hardware and software are subject to failures. However, the majority of the existing works have dealt with the problem by considering that either software is faultfree but hardware is subject to failure, or hardware is fault-free but software is subject to failure. Thus, techniques for dealing with both software and hardware faults must be developed.In this work, we propose an efficient integrated fault-tolerant approach for ultrareliable execution of tasks where both hardw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Unfortunately, the reliability and safety of computer systems cannot fit the increasing requirements. Various studies have shown that both hardware and software of computer systems are subject to fault [1][2][3][4][5][6]. However, the majority of the existing methods have dealt with the problem respectively by software diagnosis methods or hardware diagnosis methods, which ignore the relationship between software fault and hardware fault.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the reliability and safety of computer systems cannot fit the increasing requirements. Various studies have shown that both hardware and software of computer systems are subject to fault [1][2][3][4][5][6]. However, the majority of the existing methods have dealt with the problem respectively by software diagnosis methods or hardware diagnosis methods, which ignore the relationship between software fault and hardware fault.…”
Section: Introductionmentioning
confidence: 99%
“…Dugan [3] developed a simple hierarchical model to tolerate hardware and software faults, and it consisted of a small Markov chain, three fault trees and some combinatorial equations. Abulnaja et al [4] presented the Integrated Fault-Tolerant (IFT) technique, which ensured the error-free execution of tasks and concurrently diagnosed software and hardware faults. Stanton [5] presented a method based on a Petri net design approach for the detection and diagnosis of faults, and it Manuscript allows the distinction between a fault caused by a hardware failure and one caused by an error in the software.…”
Section: Introductionmentioning
confidence: 99%